PERBEDAAN KADAR UREUM DAN KREATININ SEBELUM DAN SESUDAH HEMODIALISIS PADA PASIEN GAGAL GINJAL KRONIS DI RSUD PANYABUNGAN: PERBEDAAN KADAR UREUM DAN KREATININ SEBELUM DAN SESUDAH HEMODIALISIS PADA PASIEN GAGAL GINJAL KRONIS DI RSUD PANYABUNGAN - Marisa marisa; Endang Suriani; Renowati Renowati; Vetra Susanto4; Rini Saidah (Jurnal Ilmu Kesehatan Abdurrab, 2023)
The kidneys are important organs in the human body that have the main function to excrete the rest of the body's metabolism such as urea and creatinine. Chronic kidney disease is a disorder of kidney structure or a progressive and irreversible decline in kidney function. The purpose of this study was to determine how the results of ureal levels and creatinine levels before and after hemodialysis in kidney failure patients at Panyabungan Hospital. This study used analytical methods with a cross-sectional research design with a sample size used in total sampling as 34 samples. Based on the results of a study of 34 samples, the average ureal level before hemodialysis was 180.24 mg / dL and the average ureal level after hemodialysis was 94.29 mg / dL, the average creatinine level before hemodialysis was 3.682 mg / dL and the average creatinine level after hemodialysis was 1.785 mg / dL. The conclusion of the study was that ureal levels before hemodialysis were obtained increased. Ureal levels after hemodialysis were obtained the most, namely on the criteria increased by 22 people (64.7%), normal 12 people (35.3%). Creatinine levels before hemodialysis are obtained in an elevated state. Creatinine levels after hemodialysis were obtained the most, namely on the criteria increased by 22 people (64.7%) and normal 12 people (35.3%). Indepent T test obtained sig. (2tailed) is 0.000, meaning that there is a significant and significant difference between ureal levels and creatinine levels before and after hemodialysis in chronic renal failure patients at RSUD Panyabungan